(untitled) (Semiárida, 2020)
Winter cereals are important in the subhumid dry pampas region. In La Pampa province is not cultivated durum wheat, however, it is adapted to semiarid zones of the world. The objective was to analyse management tools that allow their incorporation to pampean agrosystem, such as: genotype, sowing time and fertility. Four genotypes of durum wheat were used, in two sowing times and in two fertility conditions. The trials were conducted in the Experimental field of the Faculty of Agronomy of the UNLPam, located in 36° 32’ 49"S and 64° 18’ 20"W. The first sowing date showed greater yield than the second, but genotype interactions were detected with the time. The addition of nitrogen fertilizer increased yield in the two sowing seasons. There is genetic variability, in the earliest sowing the highest yield grain had Buck zafiro in both conditions of fertility; and in the late, Buck Esmeralda with good nitrogen fertility, and Bon. INTA cariló when there is a shortage of nitrogen. Buck Esmeralda showed good grain yield stability in the two times with good fertility conditions.